2008
DOI: 10.1111/j.1600-0536.2007.01316.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in the interleukin‐1 gene influence the stratum corneum interleukin‐1α concentration in uninvolved skin of patients with chronic irritant contact dermatitis

Abstract: We have shown a clear effect of IL1 genotype on protein expression in the SC. This altered expression may be responsible for the interindividual differences in the inflammatory response of the skin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 30 publications
1
22
0
1
Order By: Relevance
“…Following the addition of test compounds, the TNF- α levels were lower than that seen for the untreated irradiated cells. When IL-1 α (10 ng/mL) was added to the UVB-irradiated melanocyte cultures, there was an increase in TNF- α release (120-fold; Figure 3(a), Table 1) similar to that seen in cultured keratinocytes (results not shown) and previous studies [3840]. When the IL-1 α stimulated melanocyte cells were treated with α -tocopherol, CO 2 -SFE mussel oil, and 5 β -scymnol, the levels of TNF- α shed from the cells fell by 53%, 65%, and 76%, respectively (Figure 3(a), Table 1).…”
Section: Resultssupporting
confidence: 81%
“…Following the addition of test compounds, the TNF- α levels were lower than that seen for the untreated irradiated cells. When IL-1 α (10 ng/mL) was added to the UVB-irradiated melanocyte cultures, there was an increase in TNF- α release (120-fold; Figure 3(a), Table 1) similar to that seen in cultured keratinocytes (results not shown) and previous studies [3840]. When the IL-1 α stimulated melanocyte cells were treated with α -tocopherol, CO 2 -SFE mussel oil, and 5 β -scymnol, the levels of TNF- α shed from the cells fell by 53%, 65%, and 76%, respectively (Figure 3(a), Table 1).…”
Section: Resultssupporting
confidence: 81%
“…A strong association was recently identified between AD and mutations in the FLG (6,7), whereas a moderate association was found with genetic variations in the claudin 1 gene (encoding epidermal tight junctions) in mainly African Americans (8), supporting the notion that skin inflammation is often secondary to skin barrier abnormality (9). Although genetic risk factors for hand eczema and contact sensitization are not yet well-characterized, and are expected to play a more modest role for the pathogenesis, they include FLG mutations and polymorphisms in detoxification systems and immunological pathways (4,(10)(11)(12). Whether xerotic skin increases the risk of hand eczema and contact sensitization has been little-investigated, whereas the association between AD and xerosis is wellestablished.…”
mentioning
confidence: 90%
“…Accordingly, the same research group reported that carriers of a variant IL1A-889T allele have a reduced amount of IL-1α in their stratum corneum 21) . It might be speculated that an intrinsic favourable cytokine balance reflected in a high IL-1RA /IL-1α ratio due to the reduced amount of IL-1α might result in a better resistance against skin irritants.…”
Section: Genetic Factors and Icdmentioning
confidence: 99%